A positive electrode precursor material and its preparation method and application
Through the positive electrode precursor material distributed in the three elements of nickel, cobalt and manganese, the problems of structure breaking and oxygen precipitation of the positive electrode material under high voltage are solved, and high performance and stability under high voltage electricity are achieved.
Patent Information
- Application Number
- CN202211465430.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-11-22
AI Technical Summary
The existing high-voltage ternary cathode materials face structural breakage and oxygen precipitation under high voltage, resulting in unstable performance in long cycle tests.
The positive electrode precursor material with three elements of nickel, cobalt and manganese are used to distribute the region. The nickel hydroxide core, manganese hydroxide layer and cobalt hydroxide layer are formed by co-precipitation reaction, and the elements diffuse each other to form a special structure, reducing structural breakage and oxygen precipitation at high voltages.
The performance of the positive electrode material under high voltage electricity is improved, including enhanced structural stability, rate performance and cycling performance, and can maintain high capacity and good battery performance under high charge and discharge voltage.
Smart Images

Figure BDA0003956094620000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium-ion batteries and relates to a positive electrode precursor material and a preparation method and application thereof. Background Art
[0002] The rapid development and popularization of new energy vehicles have put forward higher requirements on the technical indicators of power batteries, while "endurance" and "safety" are still the pain points that have been talked about for many years in the new energy vehicle industry but have not been completely solved, which seriously hinders the process of new energy vehicles replacing fuel vehicles. Ternary materials with high nickel content (increasing the material's gram capacity) and high voltage (increasing the material's voltage) are the two main technical routes to solve the short range of automotive power batteries from the material side. The nickel content of high-voltage materials is relatively low, and the production process is not as complicated as high-nickel ternary materials. It also has a certain degree of safety and has always been widely concerned by the industry.
[0003] Although high-voltage ternary positive electrode materials can effectively improve the energy density of materials, they face a series of challenges such as crystal structure stability, phase change, interface side reactions, and oxygen release in application scenarios with voltages of 4.4V and above, which makes material development have extremely high technical barriers. At present, the industry mainly improves the capacity of ternary materials under high voltage by doping, coating, and using single crystal morphology materials, and solves problems such as high-temperature cycling, flatulence, and capacity recovery of materials. At present, doping and coating in the industry are mainly concentrated in the sintering process, while the uniformity of solid-phase doping and coating needs to be improved. In existing industrial reports, ternary materials are used at a maximum voltage of 4.4V. If the voltage continues to increase, the material performance needs to be further improved.
[0004] CN109546135A discloses a high voltage ternary material and a preparation method thereof. The method wet-dopes an aluminum source to coat a precursor and then sinter with lithium to synthesize a ternary material. The material is mainly embodied in that aluminum infiltrates and coats the ternary material, and a nickel-cobalt-manganese-aluminum material is formed in the outer layer. Although the material has improved passenger capacity and cycle performance at a higher charge cut-off voltage, the processing process mainly relies on the introduction of aluminum into the ternary material during the sintering process. Aluminum has many effects on the modification of the ternary material, but it does not form a high voltage resistant material. After a long cycle, the material is still not suitable for charging and discharging at a higher cut-off voltage, and is not suitable for the ternary material to undergo a long cycle test at a high cut-off voltage.
[0005] CN112271284A discloses a nickel-rich ternary material and its preparation method and application. The method proposes to synthesize a coating layer of a single-layer structure of lithium nickel manganate or a double-layer structure (inner layer of lithium nickel manganate and outer layer of lithium nickel manganate) on the surface of the nickel-rich ternary material. The specific process includes first synthesizing a nickel-rich ternary matrix material, and then ball-milling the nickel-rich ternary material with Mn2O7 and Na2S2O8 under an argon protective atmosphere and sintering with lithium to obtain a nickel-rich ternary material coated with lithium manganate. Add the nickel-rich ternary material or the ternary material coated with lithium manganate to a lithium, nickel and manganese salt solution for two-stage sintering to obtain the modified ternary material. The method adopts a ball milling mixing method in the single-layer lithium manganate coating process, and the process has a great damage to the morphology and structure of the nickel-rich ternary material. In the double-layer coating process, the ternary material is directly added to the lithium, nickel and manganese salt solution, stirred and then dried. The ternary material will produce side reactions directly in the mixed salt solution, especially affecting the high-nickel material. In addition, the dispersion effect is not good after direct addition, resulting in uneven coating in the later stage and even affecting the performance of the material.
[0006] Therefore, how to improve the electrochemical performance of ternary positive electrode materials under high voltage systems is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a positive electrode precursor material and a preparation method and application thereof. In the positive electrode precursor material provided by the present invention, the three elements of nickel, cobalt and manganese are regionally distributed. In the subsequent sintering process for preparing the positive electrode material, the elements diffuse with each other, and a special structure is formed during the diffusion process, which can reduce the structural fragmentation and oxygen precipitation of the material under high voltage, and finally improve the performance of the positive electrode material under high voltage.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a positive electrode precursor material, which comprises, from the inside to the outside, a nickel hydroxide core, a manganese hydroxide layer, and a cobalt hydroxide layer.
[0010] In the positive electrode precursor material provided by the present invention, the three elements of nickel, cobalt and manganese are regionally distributed. Nickel with high capacity but poor stability is distributed in the inner core, which improves the structural stability, while manganese with high stability is distributed in the middle layer, supporting the structure, and cobalt is distributed in the outermost layer, which effectively improves the rate performance of the material. In the subsequent sintering process for preparing the positive electrode material, the elements diffuse with each other, and a special structure is formed during the diffusion process, which can reduce the structural fragmentation and oxygen precipitation of the material under high voltage, and ultimately improve the performance of the positive electrode material under high voltage.
[0011] In the present invention, if the positive electrode precursor material is not distributed in the order of nickel, manganese and cobalt from the inside to the outside, the effect of the present invention cannot be achieved. If nickel hydroxide is in the outermost layer, it will lead to aggravated interface side reactions, poor thermal stability of the material, more severe flatulence and other negative effects. If cobalt hydroxide is located in the middle layer, the improvement of cycle and rate performance is limited. That is, in the precursor material of the present invention, the three elements of nickel, cobalt and manganese are synergistically distributed to jointly achieve the improvement of the performance of the positive electrode material under high voltage. Changing the order of any one of them cannot achieve the above effect.
[0012] Preferably, the nickel hydroxide core is doped with zirconium.
[0013] In the present invention, zirconium is doped into the nickel hydroxide core to stabilize the nickel structure, while doping zirconium into other positions cannot improve the structural stability of the high-nickel precursor.
[0014] Preferably, the doping amount of zirconium in the positive electrode precursor material is 500-5000 ppm, for example, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm or 5000 ppm.
[0015] Preferably, the manganese hydroxide layer is doped with aluminum.
[0016] In the present invention, aluminum is doped into the manganese layer, which improves the thermal stability of the material with minimal impact on the capacity. However, if aluminum is doped into the inner core or the outermost layer, it will affect the capacity of the material.
[0017] Preferably, the doping amount of the aluminum in the positive electrode precursor material is 3000-10000 ppm, for example, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm or 10000 ppm.
[0018] Preferably, D50 of the positive electrode precursor material is 3-4 μm, for example, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm or 4 μm.
[0019] In the present invention, the D50 of the positive electrode precursor material is 3 to 4 μm, which is helpful for obtaining a positive electrode material with a single crystal structure subsequently.
[0020] In a second aspect, the present invention provides a method for preparing the positive electrode precursor material as described in the first aspect, the preparation method comprising the following steps:
[0021] (1) adding a nickel salt solution, a precipitant solution, and a complexing agent solution to a base solution in parallel to perform a coprecipitation reaction to achieve a first target particle size;
[0022] (2) after the first target particle size in step (1) is reached, the nickel salt solution is replaced with a manganese salt solution, and the coprecipitation reaction is continued to reach a second target particle size;
[0023] (3) After reaching the second target particle size in step (2), the manganese salt solution is replaced with a cobalt salt solution, and the coprecipitation reaction is continued until the target particle size is reached, and then the reaction is stopped to obtain the positive electrode precursor material.
[0024] In the present invention, there is no particular limitation on the types of nickel salts, zirconium salts and cobalt salts, and the present invention is applicable to conventional metal salts, such as sulfates, nitrates or chlorides.
[0025] In the preparation method provided by the present invention, during the coprecipitation process, continuously introducing protective gas is a conventional technical operation, and the coprecipitation reaction of steps (2) and (3) continues the coprecipitation reaction in step (1), that is, the coprecipitation reaction continues during the entire preparation process.
[0026] The preparation method provided by the present invention sequentially performs coprecipitation reaction on the three elements of nickel, cobalt and manganese, thereby realizing the regional distribution of the three elements. The preparation method is simple, does not require complicated processing procedures, and is suitable for large-scale production.
[0027] Preferably, the pH value of the base solution in step (1) is 12 to 12.5, for example, 12, 12.1, 12.2, 12.3, 12.4 or 12.5.
[0028] Preferably, the pH value of the coprecipitation reaction in step (1) is 11-12, for example, 11, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9 or 12.
[0029] Preferably, the reaction temperature of the coprecipitation reaction in step (1) is 60-80°C, for example, 60°C, 63°C, 65°C, 68°C, 70°C, 73°C, 75°C, 78°C or 80°C.
[0030] Preferably, the rotation speed of the coprecipitation reaction in step (1) is 300-500 rpm, for example, 300 rpm, 330 rpm, 350 rpm, 380 rpm, 400 rpm, 430 rpm, 450 rpm, 480 rpm or 500 rpm.
[0031] Preferably, the concentration of the complexing agent in the base solution of step (1) is 3 to 15 g / L, for example, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L or 15 g / L.
[0032] Preferably, in step (1), the first target particle size is 2.6 to 3.5 μm, for example, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm or 3.5 μm.
[0033] In the present invention, the precipitation of the manganese hydroxide layer is carried out after the first target particle size is reached, which is more conducive to the comprehensive electrochemical performance. If the first target particle size is too small, the material capacity will be low, and if the first target particle size is too large, it will affect the battery performance such as cycle stability and thermal stability.
[0034] Preferably, during the coprecipitation reaction in step (1), a zirconium salt solution is also added in parallel.
[0035] In the present invention, the zirconium salt solution is added in parallel flow to achieve uniform doping of zirconium.
[0036] Preferably, the pH value of the coprecipitation reaction in step (2) is 10.5-11, for example, 10.5, 10.6, 10.7, 10.8, 10.9 or 11.
[0037] Preferably, in step (2), the second target particle size is 2.8 to 3.8 μm, for example, 2.8 μm, 2.9 μm, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm or 3.8 μm, etc.
[0038] In the present invention, cobalt hydroxide is precipitated after reaching the second target particle size, thereby achieving improved cycle performance and rate performance. However, if the second target particle size is too small, the safety performance of the material will decrease under high voltage, and if it is too large, it will be detrimental to capacity performance.
[0039] Preferably, during the coprecipitation reaction in step (2), an aluminum salt solution is also added in parallel.
[0040] Preferably, the aluminum salt solution and the zirconium salt solution are not added at the same time.
[0041] In the present invention, the structural stability of manganese itself is good and there is no need to add zirconium. If aluminum and zirconium are added simultaneously during the precipitation of manganese hydroxide, but zirconium is not added during the precipitation of nickel hydroxide, the structural stability of the material will be reduced.
[0042] Preferably, the pH value of the coprecipitation reaction in step (3) is 10 to 10.5, for example, 10, 10.1, 10.2, 10.3, 10.4 or 10.5.
[0043] In the present invention, the pH value in the coprecipitation process of step (1), step (2) and step (3) is regulated to achieve the regional distribution of the three elements of nickel, cobalt and manganese in the positive electrode precursor material, and obtain a product structure with a stable structure.
[0044] Preferably, the target particle size in step (3) is 3 to 4 μm, for example, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm or 4 μm.
[0045] As a preferred technical solution, the preparation method comprises the following steps:
[0046] (1) adding a nickel salt solution, a zirconium salt solution, a precipitant solution and a complexing agent solution to a base solution having a pH value of 12 to 12.5 in parallel, at a rotation speed of 300 to 500 rpm, maintaining a pH value of 11 to 12, and performing a coprecipitation reaction at 60 to 80° C. to achieve a first target particle size of 2.6 to 3.5 μm;
[0047] (2) After reaching the first target particle size in step (1), the nickel salt solution is replaced with a manganese salt solution, and the zirconium salt solution is replaced with an aluminum salt solution, and the pH value is maintained at 10.5 to 11 to continue the coprecipitation reaction to reach a second target particle size of 2.8 to 3.8 μm;
[0048] (3) After reaching the second target particle size of step (2), the manganese salt solution is replaced with a cobalt salt solution, and the addition of the aluminum salt solution is stopped. The pH value is maintained at 10 to 10.5 and the coprecipitation reaction is continued. After reaching the target particle size of 3 to 4 μm, the reaction is stopped to obtain the positive electrode precursor material.
[0049] In a third aspect, the present invention provides a positive electrode material, which is obtained by mixing and sintering the positive electrode precursor material as described in the first aspect with a lithium source.
[0050] After sintering, the positive electrode material provided by the present invention will cause the nickel, cobalt and manganese elements in the positive electrode precursor material to diffuse, and a special structure will be formed during the diffusion process, which can reduce the structural breakage and oxygen precipitation of the material under high voltage and improve the material performance.
[0051] It should be noted that the process of preparing the positive electrode material from the positive electrode precursor material is a conventional technical means:
[0052] The options of lithium source, sintering temperature and sintering atmosphere are also conventional technical choices. For example, the lithium source can be selected from lithium carbonate and / or lithium hydroxide, etc. The sintering can be divided into one-step sintering or multi-step sintering. At the same time, the positive electrode material can be coated in the subsequent sintering process.
[0053] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode material as described in the third aspect.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] In the positive electrode precursor material provided by the present invention, the three elements of nickel, cobalt and manganese are regionally distributed. Nickel with high capacity but poor stability is distributed in the inner core, which improves the structural stability, while manganese with high stability is distributed in the middle layer, supporting the structure, and cobalt is distributed in the outermost layer, which effectively improves the rate performance of the material. In the subsequent sintering process for preparing the positive electrode material, the elements diffuse with each other, and a special structure is formed during the diffusion process, which can reduce the structural fragmentation and oxygen precipitation of the material under high voltage, and ultimately improve the performance of the positive electrode material under high voltage. The positive electrode precursor material provided by the present invention has a first target particle size of 2.6-3.5 μm and a second target particle size of 2.8-3.8 μm in the preparation process, and a final particle size of the precursor material of 3-4 μm. At the same time, aluminum is doped in the manganese hydroxide layer. When the positive electrode material prepared by the precursor is used in a battery, the initial discharge specific capacity at 0.1C can reach more than 200.1 mAh / g under a high charge and discharge voltage of 3.0-4.45 V, the first efficiency can reach more than 89%, and the capacity retention rate after 50 cycles at 0.5C / 0.1C can reach more than 98.2%. DETAILED DESCRIPTION
[0056] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0057] Example 1
[0058] The present embodiment provides a positive electrode precursor material, which includes a nickel hydroxide core, a manganese hydroxide layer and a cobalt hydroxide layer from the inside to the outside (the molar ratio of nickel, cobalt and manganese is 0.6:0.1:0.3), the nickel hydroxide core is doped with zirconium, and the manganese hydroxide core is doped with aluminum. The doping amount of zirconium in the positive electrode precursor material is 500ppm, and the doping amount of aluminum in the positive electrode precursor material is 3000ppm.
[0059] The preparation method of the positive electrode precursor material is as follows:
[0060] (1) adding nickel sulfate solution, zirconium sulfate solution, ammonia solution (mass concentration 17%, concentration 8 g / L) and sodium hydroxide solution (mass concentration 32%) to a base liquid (pH value 12.3, adjusted with ammonia, sodium hydroxide and pure water, ammonia concentration in the base liquid is 10 g / L) in parallel, introducing nitrogen as a protective gas, and performing a coprecipitation reaction at a stirring rate of 400 rpm. During the reaction, the pH value was maintained at 11.5 and the reaction temperature was maintained at 70° C. until the particle size grew to 2.6 μm (first target particle size);
[0061] (2) After the particle size grows to 2.6 μm, the nickel sulfate solution is replaced with a manganese sulfate solution, and the zirconium sulfate solution is replaced with an aluminum sulfate solution, and the coprecipitation reaction is continued. At this time, the pH value during the reaction is adjusted to 10.8, and the particles continue to grow to 2.8 μm (the second target particle size);
[0062] (3) After the particles grow to 2.8 μm, stop adding manganese sulfate solution and aluminum sulfate solution, replace with adding cobalt sulfate solution, and continue the coprecipitation reaction. At this time, adjust the pH value during the reaction to 10.3. After the particles grow to 3 μm, stop the reaction, age, wash, and dry to obtain the positive electrode precursor material.
[0063] Example 2
[0064] The present embodiment provides a positive electrode precursor material, which includes a nickel hydroxide core, a manganese hydroxide layer and a cobalt hydroxide layer from the inside to the outside (the molar ratio of nickel, cobalt and manganese is 0.6:0.1:0.3), the nickel hydroxide core is doped with zirconium, and the manganese hydroxide core is doped with aluminum. The doping amount of zirconium in the positive electrode precursor material is 1500ppm, and the doping amount of aluminum in the positive electrode precursor material is 5000ppm.
[0065] The preparation method of the positive electrode precursor material is as follows:
[0066] (1) adding a nickel sulfate solution, a zirconium sulfate solution, an ammonia solution (mass concentration of 17%, concentration of 15 g / L) and a sodium hydroxide solution (mass concentration of 32%) to a base liquid (pH value of 12, adjusted with ammonia, sodium hydroxide and pure water, ammonia concentration in the base liquid of 5 g / L) in parallel, introducing nitrogen as a protective gas, and performing a coprecipitation reaction at a stirring rate of 300 rpm. During the reaction, the pH value was maintained at 11.2 and the reaction temperature was maintained at 60° C. until the particle size grew to 3 μm (first target particle size);
[0067] (2) After the particle size grows to 3 μm, the nickel sulfate solution is replaced with a manganese sulfate solution, and the zirconium sulfate solution is replaced with an aluminum sulfate solution, and the coprecipitation reaction is continued. At this time, the pH value during the reaction is adjusted to 10.6, and the particles continue to grow to 3.3 μm (the second target particle size);
[0068] (3) After the particles grow to 3.3 μm, stop adding manganese sulfate solution and aluminum sulfate solution, replace with adding cobalt sulfate solution, and continue the coprecipitation reaction. At this time, adjust the pH value during the reaction to 10.5. After the particles grow to 3.5 μm, stop the reaction, age, wash, and dry to obtain the positive electrode precursor material.
[0069] Example 3
[0070] The present embodiment provides a positive electrode precursor material, which includes a nickel hydroxide core, a manganese hydroxide layer and a cobalt hydroxide layer from the inside to the outside (the molar ratio of nickel, cobalt and manganese is 0.6:0.1:0.3), the nickel hydroxide core is doped with zirconium, and the manganese hydroxide core is doped with aluminum. The doping amount of zirconium in the positive electrode precursor material is 3000ppm, and the doping amount of aluminum in the positive electrode precursor material is 10000ppm.
[0071] The preparation method of the positive electrode precursor material is as follows:
[0072] (1) adding a nickel sulfate solution, a zirconium sulfate solution, an ammonia solution (mass concentration of 17%, concentration of 3 g / L) and a sodium hydroxide solution (mass concentration of 32%) to a base liquid (pH value of 11, adjusted with ammonia, sodium hydroxide and pure water, ammonia concentration in the base liquid of 15 g / L) in parallel, introducing nitrogen as a protective gas, and performing a coprecipitation reaction at a stirring rate of 500 rpm. During the reaction, the pH value was maintained at 12 and the reaction temperature was maintained at 80° C. until the particle size grew to 3.5 μm (first target particle size);
[0073] (2) After the particle size grows to 3.5 μm, the nickel sulfate solution is replaced with a manganese sulfate solution, and the zirconium sulfate solution is replaced with an aluminum sulfate solution, and the coprecipitation reaction is continued. At this time, the pH value during the reaction is adjusted to 11, and the particles continue to grow to 3.8 μm (the second target particle size);
[0074] (3) After the particles grow to 3.8 μm, stop adding manganese sulfate solution and aluminum sulfate solution, replace with adding cobalt sulfate solution, and continue the coprecipitation reaction. At this time, adjust the pH value during the reaction to 10. After the particles grow to 4 μm, stop the reaction, age, wash, and dry to obtain the positive electrode precursor material.
[0075] Example 4
[0076] The difference between this embodiment and embodiment 1 is that the first target particle size in step (1) of this embodiment is 2.3 μm.
[0077] The rest of the preparation methods and parameters were the same as those in Example 1.
[0078] Example 5
[0079] The difference between this embodiment and embodiment 1 is that the second target particle size in step (2) of this embodiment is 2.7 μm.
[0080] The rest of the preparation methods and parameters were the same as those in Example 1.
[0081] Example 6
[0082] The difference between this embodiment and embodiment 1 is that the reaction is stopped after the particles in step (3) of this embodiment grow to 2.9 μm.
[0083] The rest of the preparation methods and parameters were the same as those in Example 1.
[0084] Example 7
[0085] The difference between this embodiment and embodiment 3 is that the first target particle size in step (1) of this embodiment is 3.6 μm.
[0086] The rest of the preparation methods and parameters were the same as those in Example 1.
[0087] Example 8
[0088] The difference between this embodiment and embodiment 1 is that the second target particle size in step (2) of this embodiment is 3.9 μm.
[0089] The rest of the preparation methods and parameters were the same as those in Example 1.
[0090] Example 9
[0091] The difference between this embodiment and embodiment 1 is that the reaction is stopped after the particles in step (3) of this embodiment grow to 4.2 μm.
[0092] The rest of the preparation methods and parameters were the same as those in Example 1.
[0093] Example 10
[0094] The difference between this embodiment and embodiment 1 is that in this embodiment, no zirconium sulfate solution is added in step (1), and no aluminum sulfate solution is added in step (2).
[0095] The rest of the preparation methods and parameters were the same as those in Example 1.
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 1 is that the positive electrode precursor material provided in this comparative example has a mixed distribution of three elements of nickel, cobalt and manganese.
[0098] In the preparation method: nickel-cobalt-manganese mixed sulfate solution, aluminum sulfate solution and zirconium sulfate solution are added in parallel, and a coprecipitation reaction is carried out at a pH of 10.5, that is, no step-by-step coprecipitation is carried out, but a one-step reaction is carried out.
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Comparative Example 2
[0101] The difference between this comparative example and Example 1 is that in this comparative example, the process of precipitating nickel hydroxide in step (1) is adjusted to step (3), and the process of precipitating cobalt hydroxide in step (3) is adjusted to step (1), that is, cobalt hydroxide is the inner core and nickel hydroxide is the outermost layer.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Comparative Example 3
[0104] The difference between this comparative example and Example 1 is that in this comparative example, the process of precipitating manganese hydroxide in step (2) is adjusted to step (3), and the process of precipitating cobalt hydroxide in step (3) is adjusted to step (2), that is, manganese hydroxide is the middle layer and cobalt hydroxide is the outermost layer.
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Comparative Example 4
[0107] The difference between this comparative example and Example 10 is that the positive electrode precursor material provided in this comparative example has a mixed distribution of the three elements of nickel, cobalt and manganese.
[0108] In the preparation method, a nickel-cobalt-manganese mixed sulfate solution is added in parallel, and a coprecipitation reaction is carried out at a pH of 10.5, that is, no step-by-step coprecipitation is carried out, but a one-step reaction is carried out.
[0109] The rest of the preparation methods and parameters were the same as those in Example 10.
[0110] The positive electrode precursor materials provided in Examples 1-10 and Comparative Examples 1-4 were mixed with lithium hydroxide, sintered once at 800° C. for 10 h, and then sintered twice at a sintering temperature of 1000° C. for 8 h to obtain a positive electrode material.
[0111] The positive electrode materials provided in Examples 1-10 and Comparative Examples 1-4 were used to prepare positive electrode sheets, and a button-type battery was obtained using a lithium sheet as a counter electrode.
[0112] The batteries provided in Examples 1-10 and Comparative Examples 1-4 were subjected to electrochemical performance tests under the following test conditions:
[0113] (The prepared positive electrode material was mixed evenly with the conductive agent acetylene carbon black and the binder PVDF in a mass ratio of 94:3:3, and an appropriate amount of 1-methyl-2-pyrrolidone was added and ball-milled for 1 hour to form a slurry, which was evenly coated on an aluminum sheet, dried and pressed into a positive electrode sheet, and assembled into a 2032 button battery with a metal lithium sheet as the negative electrode. The electrical performance was tested using a blue electric test system, with a charge and discharge voltage of 3.0-4.45V. The first cycle was tested at 0.1C / 0.1C charge and discharge, and then 50 cycles were performed at 0.5C / 1C.) The results are shown in Table 1.
[0114] Table 1
[0115]
[0116] From the data results of Example 1 and Example 4, and Example 3 and Example 7, it can be seen that if the first target particle size is too small, it is not conducive to the cycle performance, while if the first target particle size is too large, it will lead to a decrease in capacity.
[0117] From the data results of Example 1 and Example 5, and Example 3 and Example 8, it can be seen that if the second target particle size is too small, the cycle performance will be affected, while if the second target particle size is too large, the capacity will be reduced.
[0118] From the data results of Example 1 and Example 6, and Example 3 and Example 9, it can be seen that if the particle size of the positive electrode precursor material is too small, it will affect the structural stability and be unfavorable for the cycle performance, while if it is too large, it will lead to a decrease in specific capacity.
[0119] From the data results of Example 1 and Comparative Example 1, and Example 10 and Comparative Example 4, it can be seen that the conventional positive electrode material in which the nickel, cobalt and manganese elements are directly mixed and distributed cannot achieve a stable material structure under high voltage and has a low discharge specific capacity.
[0120] From the data results of Example 1 and Comparative Examples 2-3, it can be seen that the element distribution structure of the positive electrode precursor provided by the present invention can achieve structural stability and discharge specific capacity under high voltage, while changing the order of element distribution will lead to a decrease in structural stability under high voltage, thereby resulting in a decrease in discharge specific capacity and rate performance.
[0121] To sum up, in the positive electrode precursor material provided by the present invention, the three elements of nickel, cobalt and manganese are regionally distributed. Nickel with high capacity but poor stability is distributed in the inner core, which improves the structural stability, while manganese with high stability is distributed in the middle layer, supporting the structure, and cobalt is distributed in the outermost layer, which effectively improves the rate performance of the material. In the subsequent sintering process for preparing the positive electrode material, the elements diffuse with each other, and a special structure is formed during the diffusion process, which can reduce the structural breakage and oxygen precipitation of the material under high voltage, and ultimately improve the performance of the positive electrode material under high voltage. The positive electrode precursor material provided by the present invention has a first target particle size of 2.6-3.5 μm and a second target particle size of 2.8-3.8 μm in the preparation process, and a final particle size of the precursor material of 3-4 μm. At the same time, aluminum is doped in the manganese hydroxide layer. When the positive electrode material prepared by the precursor is used in a battery, the initial discharge specific capacity at 0.1C can reach more than 200.1 mAh / g under a high charge and discharge voltage of 3.0-4.45 V, the first efficiency can reach more than 89%, and the capacity retention rate after 50 cycles at 0.5C / 0.1C can reach more than 98.2%.
[0122] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A positive electrode precursor material, characterized in that: The positive electrode precursor material includes a nickel hydroxide core, a manganese hydroxide layer and a cobalt hydroxide layer from the inside to the outside; The nickel hydroxide core is doped with zirconium; The manganese hydroxide layer is doped with aluminum; The D50 of the positive electrode precursor material is 3-4 μm.
2. The positive electrode precursor material according to claim 1, characterized in that The doping amount of zirconium in the positive electrode precursor material is 500-5000 ppm.
3. The positive electrode precursor material according to claim 1, characterized in that The doping amount of aluminum in the positive electrode precursor material is 3000-10000 ppm.
4. A method for preparing a positive electrode precursor material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) adding the nickel salt solution, the precipitant solution and the complexing agent solution to the base solution in parallel to perform a co-precipitation reaction to achieve a first target particle size; During the coprecipitation reaction in step (1), a zirconium salt solution is also added in parallel; (2) After the first target particle size in step (1) is reached, the nickel salt solution is replaced with a manganese salt solution, and the coprecipitation reaction is continued to reach a second target particle size; During the coprecipitation reaction in step (2), an aluminum salt solution is also added in parallel; (3) After reaching the second target particle size in step (2), the manganese salt solution is replaced with a cobalt salt solution, and the coprecipitation reaction is continued until the target particle size is reached, and then the reaction is stopped to obtain the positive electrode precursor material.
5. The method for preparing the positive electrode precursor material according to claim 4, characterized in that: The pH value of the base solution in step (1) is 12-12.
5.
6. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The pH value of the coprecipitation reaction in step (1) is 11-12.
7. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The reaction temperature of the coprecipitation reaction in step (1) is 60-80°C.
8. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The rotation speed of the coprecipitation reaction in step (1) is 300-500 rpm.
9. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The concentration of the complexing agent in step (1) is 3-15 g / L.
10. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The concentration of the complexing agent in the base solution of step (1) is 3-15 g / L.
11. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: Step (1) The first target particle size is 2.6-3.5 μm.
12. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The pH value of the coprecipitation reaction in step (2) is 10.5-11.
13. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: Step (2) The second target particle size is 2.8-3.8 μm.
14. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The pH value of the coprecipitation reaction in step (3) is 10-10.
5.
15. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The target particle size in step (3) is 3-4 μm.
16. The method for preparing a positive electrode precursor material according to claim 4, characterized in that: The preparation method comprises the following steps: (1) Adding nickel salt solution, zirconium salt solution, precipitant solution and complexing agent solution to a base solution with a pH value of 12 to 12.5 in parallel, at a speed of 300 to 500 rpm, maintaining the pH value at 11 to 12, and performing a co-precipitation reaction at 60 to 80° C. to achieve a first target particle size of 2.6 to 3.5 μm; (2) After the first target particle size of step (1) is reached, the nickel salt solution is replaced with a manganese salt solution, and the zirconium salt solution is replaced with an aluminum salt solution, and the pH value is maintained at 10.5-11 to continue the coprecipitation reaction to reach a second target particle size of 2.8-3.8 μm; (3) After reaching the second target particle size of step (2), the manganese salt solution is replaced with a cobalt salt solution, and the addition of the aluminum salt solution is stopped. The pH value is maintained at 10-10.5 and the coprecipitation reaction is continued. After reaching the target particle size of 3-4 μm, the reaction is stopped to obtain the positive electrode precursor material.
17. A positive electrode material, characterized in that: The positive electrode material is obtained by mixing and sintering the positive electrode precursor material according to any one of claims 1 to 3 and a lithium source.
18. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material as claimed in claim 17.
Citation Information
Patent Citations
High-voltage ternary material and preparation method thereof
CN109546135A
Modified nickel-rich ternary material as well as preparation method and application thereof
CN112271284A
Lithium ion battery positive pole material precursor and its preparation method
CN103872302A